Measurement of photon interaction parameters of high-performance polymers and their composites - Buyukyildiz, M.; Tasdelen, M. A.; Karabul, Y.; Caglar, M.; Icelli, O.; Boydas, E. (TAYLOR & FRANCIS LTD, 2018)
In the present study, commercially important high-performance polymers and their composites have been investigated with respect to photon interactions as means of mass attenuation coefficient (/), mean free path (MFP), half-value layer (HVL), effective atomic number (Z(eff)), effective electron density (N-eff), and energy absorption and exposure buildup factors (EABF and EBF) at different photon energies. For this purpose, sample plates were prepared by extrusion and injection techniques using polyethersulfone, polyetherimide, acrylonitrile butadiene styrene copolymer, polyamide 66, polyphthalamide, and polypropylene copolymers as high-performance polymers and glass and carbon fibers as reinforcement. The (/)s of the materials were measured at 81 and 356keV photon energies to determine MFP, HVL, Z(eff), and N-eff. The theoretical values of these parameters were calculated via ZXCOM, WinXCom and Monte Carlo N-Particle simulation code (MCNP), and a good agreement was obtained between WinXCom-MCNP and MCNP-Exp. Finally, EABFs and EBFs of the samples were calculated up to around 40 MFP in the energy region 0.015-15MeV and significant variations were observed in the continuous energy and MFP regions.
Keywords: Effective atomic number; high-performance polymer; mass attenuation coefficient; buildup factor; ZXCOM; MCNP; EFFECTIVE ATOMIC-NUMBER; COMPTON-SCATTERING; GAMMA-RAY; X-RAY; RADIATION; COMPUTATION; RAYLEIGH; GLASSES; PROGRAM; TESTS; Nuclear Science & Technology; Physics